MKL1 is an epigenetic mediator of TNF‐α‐induced proinflammatory transcription in macrophages by interacting with ASH2. Issue 6 (8th March 2017) - Song, Mingzi; Fang, Fei; Dai, Xin; Yu, Liming; Fang, Mingming; Xu, Yong
Abstract : Tumor necrosis factor alpha (TNF‐α) is a prototypical proinflammatory cytokine that can elicit strong inflammation in macrophages by activating NF‐κB. The underlying epigenetic mechanism is obscure. We show here that megakaryocytic leukemia 1 (MKL1) is an epigenetic mediator of TNF‐α‐induced proinflammatory transcription. Overexpression of a dominant negative form of MKL1 abrogates TNF‐α‐induced transactivation of proinflammatory genes. Proteomic analysis identifies the histone H3K4 trimethyltransferase ASH2 as a potential cofactor for MKL1. In response to TNF‐α stimulation, ASH2 is recruited by MKL1 and interacts with MKL1 to catalyze H3K4 di‐ and trimethylation. ASH2 modulates proinflammatory transcription at least in part by altering the affinity of p65 for target promoters. Together, our data support an interplay between MKL1 and ASH2 to promote TNF‐α‐induced proinflammatory transcription in macrophages. Abstract :